Challenges faced by local authorities in solid waste management: a case of Beitbridge town council. - Mulaudzi, Vimbai (Midlands State University, 2017)
Solid waste management has become a major public health and environmental concern in Zimbabwe is no exception. The magnitude of the problems being faced due to improper Solid Waste Management cannot be understated for example Open dumping and burning of municipal solid waste is a common phenomenon in most towns in Zimbabwe. The academic study regarding solid waste management has been widely researched focusing on larger cities like Harare by scholars (e.gTevera ,1991;DNR ,1994 ;Milgrud ,1995 ;Gandure ,1997 ;Mafusire ,1997;Jamare 1998 ; Kativu ,2001 ,Makwara and Magudu, 2013) hence there is lack of comparative research on small border towns. This shows that the existing research has not be exhaustive and is limited on geographical coverage .As a result ,there is lack of information on Solid waste management affecting small towns especially border towns. However in addressing this issue a research was conducted in Beitbridge. The aim was to assess the challenges in which Beitbridge town council face in addressing solid waste management, some of the challenges are poor management practices such as burning of municipal and illegal dumping, the council lacks machinery for refuse collection such as trucks, compactors etc., poor community engagement in solid waste due to ignorance and lack of awareness. A total of 30 questionnaires were given to the targeted population which includes residents and council staff. Interviews were also conducted. It was noted that the council is selling bins to the community at an unaffordable price; therefore some people are failing to purchase them, hence end up doing illegal dumping because they do not have the proper bins. The recommendation which was given is that the local authority to sell bins at an affordable price.